Suicide and Its Nexus: A Theoretical Reconstruction of Suicide - Lestari, Nastiti Soegeng (Masyarakat: Jurnal Sosiologi, 2024)
In Indonesia, suicide research has largely overlooked structural factors at the meso and macro levels, whether as primary causes, contributing factors, or considerations for prevention strategies. The dominance of psychological and psychiatric approaches has marginalized sociological perspectives, limiting a more holistic understanding of suicide. Existing heuristic models primarily frame suicide as a consequence of mental health disorders or economic conditions, reinforcing a dichotomy: one perspective views suicide as a psychological and/or psychiatric phenomenon, while the other treats it as a sociological fact. However, suicide encompasses a far more complex reality that transcends this binary. This study offers a comprehensive theoretical reconstruction, demonstrating that suicide is not merely a psychological, psychiatric, or social issue but an interdisciplinary phenomenon. Through a literature review, this paper proposes an integrative theoretical model that bridges disciplinary divides and provides a framework for more effective prevention strategies. Ultimately, this study argues that an interdisciplinary approach is not only preferable but essential for addressing the multidimensional nature of suicide.